Monetary policy and housing prices: a case study of Chinese experience in 1999-2010 - Yanbing Zhang; Xiuping Hua; Liang Zhao (Bank of Finland, Institute for Economies in Transition (BOFIT), 2011)
How do monetary policy variables affect housing prices? In this paper we apply a non-linear model-ling approach, the Nonlinear Auto Regressive Moving Average with eXogenous inputs (NAR-MAX), to investigate determinants of housing prices in China over the period 1999:01 to 2010:06. The NARMAX approach has an advantage over prevailing methods in that it automatically selects linear and non-linear forms of variables and the numbers of corresponding lags according to statistical properties. Both linear and non-linear estimation results identify a number of key monetary and price variables, including most notably mortgage rate, producer price, broad money supply and real effective exchange rate. Meanwhile, some key real economic variables such as income are not independently significant. Our findings should be helpful in understanding the formation of housing prices in China and will provide some valuable insights on how to use monetary policies to manage asset prices.
URN:NBN:fi:bof-201408072124
Keywords: 330